Capturing the experiences of FASD prevention workers through quilting - Atkinson, Erin; Job, Jenelle; Pei, Jacqueline; Poth, Cheryl; O’Riordan, Teresa; Taylor, Lin (First Peoples Child & Family Review, 2013)
Visual data collection methods are gaining momentum in the field of qualitative research because of their ability to document the social world and experiences of participants (Banks, 2001; Rose, 2001. This study employed quilting as a data collection method to capture the experiences of 47 Fetal Alcohol Spectrum Disorder (FASD) prevention workers in the Parent Child Assistance Program (PCAP) across Alberta. Specifically, this article focuses on the process of creating the quilt, the impact that this data collection method has had on participants and researchers, as well as a discussion of our next steps and suggestions for future opportunities to use quilting methods in community-based research.